David W. Phillipson (ed.): The Monuments of Aksum. Based on the work in A.D. 1906 of the Deutsche Aksum-Expedition by Enno Littmann, Daniel Krencker and Theodor von Lüpke (Berlin 1913) - Hahn, Wolfgang (Aethiopica, 2000)
Review